THE EFFECTIVENESS OF GREEN OPEN SPACE (RTH) MANAGEMENT BY THE SUKABUMI CITY PUBLIC WORKS AND SPATIAL PLANNING OFFICE 2020-2023 - Yana Fajar FY Basori; Randhika M Lesmana Putra Randhika M Lesmana; Resa Fitriani; Adinda Raya Marsela (DIA: Jurnal Administrasi Publik, 2025)
A green city environment is needed throughout the city, clean and cool air quality is the result of the availability of a green city which has benefits for health, both bodily health and environmental health. The existence of clean air areas and healthy cities is something that society needs. As regulated in Law Number 26 of 2007 concerning the arrangement of urban green open spaces. This research was motivated by the lack of management of green open spaces in the city of Sukabumi. This research aims to determine the effectiveness of green open space (RTH) management by the Sukabumi City Public Works and Spatial Planning Department. This research uses Nugroho's theory of effectiveness with three dimensions, namely right policy, right implementation, right target, right environment and right process. This research method uses descriptive qualitative with interview, observation and documentation techniques. The results of the research show that the management of Green Open Space in Sukabumi City is not optimal. Because in the management process, there is still a lack of human resources as cleaning staff, apart from that there is a lack of public awareness to maintain cleanliness and maintain the green open space facilities that have been provided.